(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2024)
Christian Metz can rightfully be considered the founder of the semiology of cinema. This essay traces the supporting structures, and the problems connected to them, of this theoretical effort, starting first of all from the context that nourished it. The difficulties associated with both the construction of a general semiology and the use of its categories in cinema and artistic languages emerge.